Practical aspects of rape investigation : a multidisciplinary approach - Burgess, Ann Wolbert; Hazelwood, Robert R. (Boca Raton : CRC Press, 2009)
A resource on rape investigation. It brings into focus the five different principals involved in a rape investigation: the police investigator, examining nurse, forensic scientist, crisis counselor, and prosecutor. It demonstrates how professionals can work together to effectively handle even the complex sexual assault crime
1. The victim -- 2. Investigation -- 3. Forensic and court -- 4. Special populations
Includes bibliographical references and index
Keywords: Rape -- Investigation; Rape -- United States -- Investigation